Pengaruh Jumlah Penduduk, UMK dan Tingkat Pengangguran Terbuka Terhadap Penyerapan Tenaga Kerja di Provinsi Jawa Tengah - Tobing, Natalia Wedina; Hanifa, Nurul (Universitas Negeri Surabaya, 2024)
The purpose of this study was to ascertain how labor absorption in 35 regencies and cities in the province of Central Java was impacted by population, regency/city minimum wages, and open unemployment rates between 2018 and 2022. Utilizing a quantitative methodology, this study makes use of secondary data that was collected from the Central Bureau of Statistics. Panel data regression is the data analysis technique used in this investigation. The findings indicated that while the district/city minimum wage and the open unemployment rate had a beneficial impact on labor absorption, the population had a partially negative effect. In the Province of Central Java, all three variables simultaneously have a beneficial impact on labor absorption.